ASPEK HUKUM MENGENAI KOMPENSASI BAGI WARGA YANG MENDUDUKI LAHAN NEGARA DI PERKOTAAN DAN PERDESAAN YANG TERKENA PROYEK - HENDRAKUSUMAH, ERNAWATI; MULIYA, LIYA SUKMA (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2011)
In Indonesia, there many cases of the existence of the state/government of land use by the public people. Problems arise when there is a decision-rights community's land is used by the government for public purposes, such as project water dams for hydroelectric power. This problem often creates polemic on the issue of compensation for people who take advantage of the country's land. The question: Should people be compensated? What kind of compensation like? And how it can be done? This paper aims to examine the legal aspects of the compensation for the people who occupy state land (government) in the District of West Bandung regency cavity affected Upper Cisokan Pumped Starage of West Java Province.